The East African Highland cooking bananas ‘Matooke’ preferences of farmers and traders: Implications for variety development - Akankwasa, Kenneth; Marimo, Pricilla; Tumuhimbise, Robooni; Asasira, Moreen; Khakasa, Elizabeth; Mpirirwe, Innocent; Kleih, Uli K.; Forsythe, Lora; Fliedel, Geneviève; Dufour, Dominique; Nowakunda, Kephas (Wiley, 2021)
‘Matooke’ is a staple food made from Highland cooking bananas in the Great Lakes region of East Africa. Genetic improvement of these bananas for resistance to pests and diseases has been a priority breeding objective. However, there is insufficient information on fruit quality characteristics that different users prefer, resulting in sub‐optimal adoption of new varieties. This study identified matooke characteristics preferred by farmers and traders, using survey data from 123 farmers, 14 focus group discussions and 40 traders. Gender differences were considered. The main characteristics that were found to drive variety preferences were agronomic (big bunch, big fruits) and quality (soft texture, good taste, good aroma, yellow food). There were minimal geographical and gender differences for trait preferences. Quality characteristics need to be defined in terms of physical–chemical underpinnings so that breeding programmes can apply accurate high‐throughput systems, thereby improving adoption and impact of new banana varieties.